Dinamika Sosial Masyarakat Multikultural Dalam Penyatuan Nagari - Ridwan Ridwan; Zumri Munajab (Kemudi, 2019)
Nagari is a customary law community unit that lives within the Minangkabau community unit area which has clear natural boundaries, under the leadership of the chief, has its own rules and carries out arrangements based on consensus. In its development there is a lot of unification of several nagari into one nagari like in the Nagari Ranah Palabi. The reason for the union of the two Nagari into one Nagari was due to the impact of regional expansion which eventually directly changed the geographical pattern of the region. Considering the territory of the Palabi Territory whose territory is insufficient for criteria, it was finally put together with the village of Bukit Tujuh (sp8). From the merging or unification of the two villages between the villages of Ranah Palabi (SP 6) and the Village of Bukit Tujuh (SP 8), a new dynamic was created, both in terms of social, customs and customs. The occurrence of such assimilation certainly raises new social dynamics and is certainly different from the dynamics of the origin of each village so that it can foster customs, lifestyles and habits of the community itself. The formulation of the problem in this research is how is the social dynamics of the community as a result of the union of two villages? and what are the steps of the Nagari government in dealing with these social dynamics? The method in this study uses a qualitative descriptive method. Nagari Ranah Palabi is a nagari formed from the merger of two nagari, namely Nagari Ranah Palabi sp6 and Bukit Tujuh sp8. The research found that the unification gave rise to social dynamics of the community which disrupted the development and development of the country, especially towards the Nagari Ranah Palabi community. The social dynamics can be seen in all aspects such as the aspects of development, religion and youth. In the development aspect many developments are carried out based on a (primordial) kinship system where if there is a representative of their region who becomes a village apparatus or in the Nagari government, development must be carried out in their area as well as the struggle for the implementation of development by each of the respective regions. For this reason, it is necessary to have actions or efforts by the Nagari Ranah Palabi government to solve these problems so that the achievement of a unified, peaceful and equitable community. The role of the Nagari Government is very necessary in this matter because the Nagari government is the highest government institution in or in the Nagari.